VNTRbased diversity analysis of 2x and 4x fullsib Musa hybrids - Crouch, J.; Crouch, H.; Tenkouano, A.; Ortíz, R. (1999)
The triploid plantain landrace Obino l Ewai (Musa spp., AAB genome) has been crossed with a wild diploid banana (M. acuminata subsp. burmannica var. Calcutta 4 , AA genome) to generate full-sib diploid and tetraploid hybrids combining good agronomic performance and disease resistance. Microsatellite marker analysis of the parental genotypes confirmed the highly heterozygous nature of both parental genotypes. Comparative analysis of 2x and 4x full-sib hybrids with their parental genotypes indicated that tetraploid hybrids are generally more closely related to Obino l Ewai than their diploid full-sibs. Based on VNTR analysis it is possible to identify those hybrids, which may be most useful in subsequent breeding of secondary triploid hybrids. There was a significant (P<0.05) negative association between the VNTR-based genetic similarity of hybrids to Obino l Ewai and a phenotypic distance index based on eight agronomic descriptors. However, there was no association between the molecular genetic similarity of hybrids to Calcutta 4 and the respective phenotypic distance index. Many microsatellite markers generated an unexpectedly high number of amplification products from AA and AAB genotypes plus their progeny which may suggest the presence of a high frequency of loci duplication in both A and B genomes, in addition to the detection of heterozygous and/or homoeologous loci.